A molecular roadmap for the emergence of early-embryonic-like cells in culture. (January 2018) - Rodriguez-Terrones, Diego; Gaume, Xavier; Ishiuchi, Takashi; Weiss, Amélie; Kopp, Arnaud; Kruse, Kai; Penning, Audrey; Vaquerizas, Juan; Brino, Laurent; Torres-Padilla, Maria-Elena
Abstract Unlike pluripotent cells, which generate only embryonic tissues, totipotent cells can generate a full organism, including extra-embryonic tissues. A rare population of cells resembling 2-cell-stage embryos arises in pluripotent embryonic stem (ES) cell cultures. These 2-cell-like cells display molecular features of totipotency and broader developmental plasticity. However, their specific nature and the process through which they arise remain outstanding questions. Here we identified intermediate cellular states and molecular determinants during the emergence of 2-cell-like cells. By deploying a quantitative single-cell expression approach, we identified an intermediate population characterized by expression of the transcription factor ZSCAN4 as a precursor of 2-cell-like cells. By using a small interfering RNA (siRNA) screen, we identified epigenetic regulators of 2-cell-like cell emergence, including the non-canonical PRC1 complex PRC1.6 and the EP400–TIP60 complex. Our data shed light on the mechanisms that underlie exit from the ES cell state toward the formation of early-embryonic-like cells in culture and identify key epigenetic pathways that promote this transition. Rare cells resembling the 2-cell-stage embryo (2 C) arise in embryonic stem cell cultures. By performing single-cell analyses and an siRNA screen, the authors identify the intermediate cellular states and epigenetic regulators that underpin the transition to a 2C-like state.